Biometric Indices and Condition factors of Pomadasys jubelini (Cuvier, 1830) from Obuama Creek, Nigeria - Olaniyi Alaba Olopade; Henry Eyina Dienye; Cynthia Chigazu Okonkwo (Marine Science Department Diponegoro University, 2020)
Biometric indices of Pomadasys jubelini from Obuama Creek, Rivers state, Nigeria were investigated using length frequency distributions (LFDs), length-weight relationships (LWRs), length-length relationships (LLRs), condition factors (allometric, KA, Fulton’s, KF and relative, KR). Specimens were captured in a stretch of the creek from March to September 2019. A total of 229 specimens were examined with the total length (TL) and weight (W) ranging from 8.7 to 50.4 cm and 8.7 to 834.5 g respectively. The standard length (SL) ranged from 5.3 to 46.8 cm, fork length (FL) was between 6.5 to 48.7 cm and the girth length (GL) varied from 4.7 to 38.7 cm. The relationships of weight-length showed a negative allometric growth pattern with a value of